Micro-platformization for digital activism on social media. Issue 1 (2nd January 2021) - Hutchinson, Jonathon
ABSTRACT: Social media emerged with a broad understanding that egalitarian practices would become the standard approach to publishing and distributing content. In recent times we have seen this flat hierarchical approach fade as commercial stakeholders, platform providers and content publishers continue to design and practice exclusionary processes to ensure their work is visible. This current practice limits the capacity for all voices to be heard, prompting the question how can digital activism remain visible in a media-saturated social media environment? This paper draws on a content analysis of the most popular YouTube users in Australia to illustrate the absence of digital activism within its visual culture. It maps the process of fragmented platformization, called here micro-platformization, to highlight the content production and publishing strategies digital activists should adopt. While successful commercial YouTube practitioners adhere closely to the principles of social media logics (Van Dijck, J., & Poell, T. (2014). Understanding Social Media Logic. Media and Communication, 1 (1), 2–14), this paper argues that stakeholders engaging in the practice of digital activism need to adopt similar strategies to their commercial counterparts. By including strategies that reflect the successful practices of social media logics, digital activism can not only become visible across social media spaces, but also engage public discourse on civic matters and public affairs.